Horizontal distribution of megalopae of Brachyura (Crustacea, Decapoda) in a South American tropical estuary - Nunes Pralon, Bruno Gabriel [UNESP]; Hirose, Gustavo Luis [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Taylor & Francis As, 2012)
The available information on the larval phase of estuarine crabs in tropical habitats is scarce, despite its importance for the population dynamics of these crustaceans. The goal of the present study was to evaluate patterns of spatial distribution of megalopae along a gradient in the Ubatumirim River estuary, Ubatuba region, state of São Paulo,Brazil. Samples were taken periodically during neap and spring tides in April and November 2005. The megalopae were collected on passive collectors made from an organic substrate, at 10 sampling sites equally spaced along the two river channels of the Ubatumirim estuary. At the laboratory, larvae were identified according to available literature. Sesarmid and ocypodid crabs predominated in the samples. Megalopae settled differently in neap- and spring-tide periods, with a tendency toward increased settlement during high-amplitude tides. The highest density of megalopae was recorded at the sites near the river mouth. The observed horizontal distribution pattern probably results from the influence of seawater or from mechanisms to avoid predation and/or competition for resources. Despite problems in identifying taxa to species level, the results of the present study contribute to increase knowledge about overall trends in the horizontal distribution of megalopae in estuarine systems.
Keywords: Settlement; artificial collectors; abiotic factors; larval ecology